Effect of LiH on the fast hydrolysis and hydrogen generation of MgH2 by ball milling. (11th October 2022) - Qiu, Hongwei; Han, Xingbo; Zang, Shuyan; Liu, Wei; Yang, Guo; Lv, Lijun; Wang, Xiaofeng; Duan, Jiaqi; Wang, Shuangyu
Abstract : The MgH2 –LiH composites with different composition ratios were prepared by different ball milling times, and the hydrogen generation performances of the composites were investigated and compared. Abstract : The MgH2 –LiH composites with different composition ratios were prepared by different ball milling times, and the hydrogen generation performances of the composites were investigated and compared. X-ray diffraction, scanning electron microscopy and X-ray photoelectron spectroscopy techniques were adopted to elucidate the performance improvement mechanisms. The results show that the hydrogen generation yield and kinetics can be improved with the increase of LiH content significantly. For the 7MgH2 –3LiH and 1MgH2 –1LiH, with the increase of the ball milling time, the hydrogen yield increases firstly, and then decreases, but the kinetics almost do not change. This may be caused by the change of particle size of the composites after ball milling. However, for the 9MgH2 –1LiH, the hydrogen yield increases with ball milling time but the kinetics decrease gradually. This may be due to the gradual movement of LiH from the surface to the interior of MgH2 and to the covering of MgH2 after ball milling.